(untitled) (Numerus academy review, 2026)
The creator owns the reins of language, savors it in the act of receiving and uses it carefully in the act of spoken and written production. The research aims to talk about the poet Ibrahim Toukan being a linguist in his directives; For his efforts that suggest the depth of his linguistic thought, and to explain this by highlighting the linguistic directives of Ibrahim Toukan in his works and achievements, using the descriptive analytical approach and interrogating the texts in which he presented linguistic issues and issues and extrapolating their features in the applied aspects of his creations, and then the conclusion of the research And it includes the results and recommendations, and an index of sources and references.